Productivity and photosynthetic pigments in bell pepper plants grown in soil with biofertilizer and protected against water loss - de Lima Neto, Antonio João; Guedes Dantas, Tony Andreson; Ferreira Cavalcante, Lourival; Araújo Diniz, Adriana; Guedes Dantas, Stênio Andrey; de Luna Souto, Antônio Gustavo (Revista Ceres, 2025)
The search for techniques that maximize the use of water is becoming necessary for the sustainability of agriculture in semi-arid areas. In this sense, the present work aimed to evaluate the effects of soil protection against water loss and the use of bovine biofertilizer on fruit production and chlorophyll content in bell pepper plants. The experiment was conducted in the municipal district of Nova Floresta in the semi-arid region of the State of Paraíba during the period of August 2010 to February 2011. The experimental design was a randomized block design with four repetitions in a 2 × 2 × 2 factorial scheme, corresponding to soil without and with bovine biofertilizer, without and with mulch, and without and with side coating of the grooves with polyethylene film, to reduce water loss through evaporation and lateral movement of water. The results showed that the use of side coatings of the grooves led to greater production, generating productivity gains in bell pepper cultivation. The association between side coating of the grooves and mulching of the soil resulted in increased levels of chlorophyll, but the bovine biofertilizer × side coating × mulch interaction inhibited the production of chlorophyll in the plants.